PROFESSIONAL ORIENTATION OF CHILDREN WITH SPECIAL NEEDS BY MEANS OF STEAM EDUCATION - Hnatiuk, Oksana; Kolmakova, Vira; Reshitnyk, Yuliia; Bilyk, Karina (Physical and Mathematical Education, 2025)
Formulation of the problem. The paper considers the issue of professional orientation of children with special educational needs (SEN) in the context of socio-cultural activities and reforms of the New Ukrainian School. The need to use adapted approaches to professional orientation that take into account the individual characteristics of students' development is emphasized. The use of STEAM education is proposed as an effective tool for forming professional motivation and conscious choice of future profession by children with special educational needs. The relevance of the problem is due to the need to ensure equal access to quality education and create a barrier-free educational space. In the context of inclusive education, effective professional orientation of students requires special attention, which should take into account the psychophysical characteristics of children, the requirements of the labor market, and modern educational technologies. However, existing approaches to professional self-determination of children with SEN are often outdated and do not correspond to modern trends, in particular, the possibilities of STEAM education. Insufficient interaction between educational institutions, social services, and employers in the process of professional integration of such students was revealed, which complicates their adaptation and employment after completing their studies in educational institutions.Materials and methods. The study used a comprehensive approach, including an analysis of scientific and methodological literature, empirical methods, and pedagogical experiments. STEAM sets (electronic, magnetic constructors) and ecological materials for design and programming were used.Results.  Results confirm that STEAM education contributes to the development of compensatory skills in children with SEN, increases their motivation, and adaptation to the educational process. Interactive methods and practical classes help students acquire new competencies, effectively interact with peers, and, in the future, improve their competitiveness in the labor market. The introduction of STEAM education contributes to the better socialization of children with SEN and their subsequent successful professional development.Conclusion. STEAM education, as a tool for professional orientation for children with special educational needs, is a promising direction in the development of Ukrainian education. Its psychodidactic component and contact learning of disciplines facilitate the integration of children with special educational needs into society.
Keywords: professional orientation; children with special educational needs; inclusive education; STEAM education; professional self-determination; social adaptation; competencies; labor market; interactive technologies; constructors